Short-term treatment effects of the quad-helix appliance on dentofacial morphology of hyperdivergent patients - Endo Saori; Yamada Wataru; Shundo Isao; Kobayashi Yoshiki; Komatsuzaki Akira; Endo Toshiya (Sciendo, 2016)
The purpose of this study was to evaluate the effects of short-term expansion treatment using the quad-helix appliance on dentofacial morphology in orthodontic patients presenting with a hyperdivergent facial pattern.